The Glass Ceiling and Challenges Which Women Posed to Have Presences in Political Leaderships in Afghanistan - Sokhanwar, M. Davood; Mahya, Yalda (European Journal of Social Science Education and Research, 2024)
This study evaluate the challenges posed to women’s participation in Afghans’ leadership, it’s like a glass ceiling that prevents their presence at the top organizational level of the national entities. The aim of this research is to recognize the mentioned challenges and propose precise solutions on those regarded. The research is conducted based on disk research method and have gone through first hand highly accredited existing national and international documentaries, and the researches which are conducted by central statistics office of Afghanistan (CSO), independent human right commission of Afghanistan, Afghanistan research and evaluation unit (AREU), integrity watch of Afghanistan and other related academic articles and journals. The study concludes that, despite the efforts made in recent years, the presence of women on different hierarchical level of entities and leaderships steps are less and symbolic, and the key factors regarding to those could be cultural and educational obstacles and as well as security challenges. On this study the researchers on first steps tried to identify the obstacles and then proposed applicable realistic suggestions based on Afghanistan’s social context.